A Woman's Game : the rise, fall and rise again of women's soccer - Wrack, Suzanne (London : Faber & Faber Ltd, 2022)
"Women's soccer is a game that has so often been relegated to the margins in a world fixated on gender differences above passion and talent. It is a game that could attract 50,000 fans to a stadium in the 1920s, was later banned by England's Football Association grounds for being "unsuitable for females," and has emerged as a global force in the modern era with the US Women's National Team leading the charge. A Woman's Game traces this arc of changing attitudes, increasing professionalism, and international growth. Veteran journalist Suzanne Wrack has crafted a thoroughly reported history which pushes back at centuries of boundaries while celebrating the many wonders that women's soccer has to offer. With the enormous success of the World Cup, 82 million US viewers for the USWNT against Netherlands in the 2019 World Cup Final, enlightened and outspoken players like Megan Rapinoe helping raise the profile of the game across the world, and a fully professional top-tier league going from strength to strength in both the US and the UK, the time cannot be better for this in-depth look at the beautiful game"--
Keywords: Soccer for women; Soccer for women -- History